Ordinary vertical urbanisms: City apartments and the everyday geographies of high-rise families. (August 2016) - Nethercote, Megan; Horne, Ralph
In many new world cities, inner city apartment development proceeds at unprecedented rates. In dominant urban planning and property development discourses, new inner city dwellers are consumption-orientated young professionals and "empty nesters"—all similarly childless. Nonetheless, families make their homes in city apartments, and their experiences are not well understood. Meanwhile, within urban and political geography, new interest in verticality has directed attention to the changing urban topography and volumetric profile of cities. However, a topographic bias occludes the mundane, intensive relations that enervate these everyday lived spaces (i.e. ordinary topologies), while a fascination with spectacular urbanisms and cities in conflict neglects other "ordinary" vertical urbanisms. Drawing on a qualitative study of high-rise families in inner city Melbourne (Australia), this article responds both to calls for a more topological rendering of vertical urbanisms and the neglected experiences of vertical urban families. We detail the intimate and material geographies of high-rise family living and highlight how the topologies of high-rise living and the topographies of urban intensification projects intersect, including with benign and hopeful prospects for the contemporary city.